Antologizzare il proprio passato. Macrostrutture liriche e temporalità del lutto (ENTHYMEMA, 2017)
Psychoanalytic Nachträglichkeit appears to be the temporality that structures the canzonieri in morte, that is to say, collections of poems devoted to the poet’s dead beloved. In fact, a similar process of (self)-interpretation that is both retrospective and progressive at the same time can be found much earlier in European poetry. The article starts from certain theoretical reflections and an overview of the two fundamental models provided by Dante’s Vita Nova and Petrarch’s Canzoniere in order to focus on some poems from two contemporary Italian canzonieri in morte: Eugenio Montale’s Xenia (in Satura, 1971) e Milo De Angelis’ Tema dell’addio (2005). The intent is to show how the complex temporality that Freud named Nachträglichkeit can perform different essential functions: to organize the lyric macro-text; to construct a new meaning for poems previously composed; to reconsider the poet’s own personal and poetic past; and to contribute to the creation of a new author. Certain features delineated in the canzonieri will finally lead to reflect upon the ‘self-anthology’ as a form, that is to say, an anthology of the poet’s work selected and organized by the poet him/herself.